Process for the preparation of a coordination polymer material with delayed fluorescence properties and use thereof

CN117659424BActive Publication Date: 2026-10-27NANKAI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311415994.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-30
Publication Date
2026-10-27
Estimated Expiration
2043-10-30

AI Technical Summary

Technical Problem

过氧化物等强氧化剂能够氧化降解HD,但是很难做到100%的选择性氧化

Benefits of technology

[0011]本发明的技术效果:该材料是一种催化降解芥子气模拟物CEES的基于主-客体作用的延迟荧光材料,在360nm紫外光或420nm蓝光的激发下能够产生寿命为200ns左右的延迟荧光,有效的利用了三线态能级,三线态激子通过能量转移将基态氧(3O2)转化为单线态氧(1O2),而1O2能够选择性的将芥子气模拟物CEES转变成无毒的2 氯乙基乙基亚砜(CEESO),而不产生2-氯乙基乙基砜(CEESO2),因此,该材料能够高效快速地光催化降解芥子气模拟物。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117659424B_ABST
    Figure CN117659424B_ABST
Patent Text Reader

Abstract

The application discloses a coordination polymer material with delayed fluorescence performance, which is a host-guest coordination polymer with a space hexahedron configuration, has a crystal length of 50-200 mu m, and can keep the original space configuration in air and has good stability; the structural formula of the material is: The application discloses a host-guest action-based delayed fluorescence material for catalytic degradation of mustard gas simulant CEES; after irradiation, singlet excitons are converted into triplet excitons, an energy transfer process is promoted, and oxygen molecules are activated to generate 1 O2, 1 O2 can selectively convert mustard gas simulant CEES into non-toxic 2-chloroethyl ethyl sulfoxide (CEESO), without generating 2-chloroethyl ethyl sulfone (CEESO2), so that the material can efficiently and rapidly photocatalyze and degrade mustard gas simulant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of host-guest coordination polymer materials, and in particular to a method for preparing a coordination polymer material with delayed fluorescence properties and its application. Background Technology

[0002] Chemical warfare agents (CWAs) are a collective term for destructive chemical substances that can cause toxicity to humans and animals during warfare. They can seriously endanger national and environmental security, making research on the degradation of various chemical warfare agents of great significance. Mustard gas (HD) is a typical vesicant chemical warfare agent that attacks mucous membranes, causing irreversible alkylation reactions in human DNA, RNA, and proteins, leading to cell death. Short-term exposure to high doses of HD can be fatal. Mustard gas is characterized by its recalcitrant degradation and persistent stability in the environment. The products obtained from the oxidation degradation of HD are mainly sulfoxides and sulfones. The partial oxidation product of HD, di(2-chloroethyl) sulfoxide (HDO), is almost non-toxic, while the complete oxidation product, di(2-chloroethyl) sulfone (HDO2), is highly toxic. Therefore, selective oxidation to convert HD into non-toxic HDO without producing the highly toxic peroxide product HDO2 is the ideal degradation pathway for mustard gas.

[0003] Finding catalytic materials for the mild, efficient, and highly selective degradation of toxic oxidants (HD) is crucial. Strong oxidants such as peroxides can oxidatively degrade HD, but achieving 100% selective oxidation is difficult. Singlet oxygen is the most studied and most effective oxidant. 1 O2 can partially oxidize HD to HDO without producing HDO2. The energy transfer process of the photosensitizer excites molecular oxygen to produce singlet oxygen. 1 O2 can enable control over product selectivity. 1 Compared to other reactive oxygen species, O2 has moderate oxidizing power, making it more suitable for achieving high selectivity and high conversion rates in certain oxidation reactions. 1 In terms of O2 production, direct exciton energy transfer is more favorable. 1 Efficient O2 generation. Delayed fluorescence materials possess a smaller ΔE. S1-T1 The conversion between energies S1 and T1 is easier, enabling efficient intersystem crossing (ISC) and reverse intersystem crossing (RISC) processes. Excited photosensitizer molecules in the triplet state can transfer energy to the ground state. 3 O2, easily produced 1 O2. Summary of the Invention

[0004] To achieve the synthesis of a highly selective and fast-degrading catalytic degradation material for the mustard gas mimic 2-chloroethyl ethyl sulfide (CEES), this invention discloses a method for preparing a coordination polymer material with delayed fluorescence properties and its application. The good stability of this material in air makes it suitable for recycling as a heterogeneous catalyst, and it has a promising application prospect in the catalytic degradation of chemical warfare agents.

[0005] The technical solution of this invention is: a coordination polymer material with delayed fluorescence properties. It is a host-guest coordination polymer exhibiting a spatial hexahedral configuration, with a crystal length of 50 μm to 200 μm, and can maintain its original spatial configuration in air, demonstrating good stability. The structural formula of this material is: [Cd₄(TPP)₂(PTA)₃(H₂O)₄]. n ·x(Phcz),x=1-2; Among them, TPP=6'-(pyridin-4-yl)-4,2':4',4''-terpyridine, PTA=terephthalicacid, Phcz=9-phenyl-9H-carbazole.

[0006] The coordination polymer material with delayed fluorescence properties is prepared from 2,4,6-tris(pyridin-4-yl)pyridine (TPP), terephthalic acid (PTA), N-phenylcarbazole (Phcz), and cadmium salt.

[0007] A method for preparing a coordination polymer material with delayed fluorescence properties, namely MOF material [Cd4(TPP)2(PTA)3(H2O)4] n The preparation method of x(Phcz), x=1-2 includes the following steps: (1) Dissolve 0.05-0.1 mmol PTA in 3-5 ml DMF solvent, dissolve 0.05-0.1 mmol cadmium salt in 3-5 ml deionized water, mix the two and add 0.03-0.06 mmol TPP, then add 3-5 ml EtOH, mix in a 20 ml vial, sonicate for 15-20 minutes, and then place in a 92-100℃ oven for a solvothermal reaction for 12-24 hours; (2) After the reaction is complete, yellow-green rod-shaped crystals are obtained. The crystals are washed and filtered with DMF, water or anhydrous ethanol solvent. After drying for 3-5 hours, the product is collected and ground to obtain yellow-green powder, which is the coordination polymer material with delayed fluorescence properties.

[0008] The coordination polymer material with delayed fluorescence properties is applied to efficient singlet oxygen catalytic oxidation reactions and catalytic degradation of chemical warfare agents. When excited by ultraviolet light at a wavelength of 360 nm or blue light at a wavelength of 420 nm, fluorescence and time-resolved spectroscopy tests were performed on the material, and fitting curves showed that the average lifetime of delayed fluorescence was 180–240 ns.

[0009] The coordination polymer material with delayed fluorescence properties is applied to a highly efficient singlet oxygen catalytic oxidation reaction. Using the coordination polymer material with delayed fluorescence properties as a catalyst, 10-15 mg of the MOF material is placed in 1-2 ml of deuterated methanol solution, methanol solution, or acetonitrile solution, or not placed in a solvent, and then added to a 2,2,6,6-tetramethylpiperidine (TEMP) (20-50 mmol / L) solution. In an oxygen atmosphere, the mixture is irradiated with ultraviolet light emitting a wavelength of 360 nm or blue light emitting a wavelength of 420 nm. TEMP captures singlet oxygen. 1 The generation of TEMPO from O2 indicates that the MOF material can generate singlet oxygen through luminescence quenching. 1 O2.

[0010] The coordination polymer material with delayed fluorescence properties is applied to the catalytic degradation of chemical warfare agents. 10–15 mg of the MOF material is placed in 1–2 ml of deuterated methanol solution, methanol solution, or acetonitrile solution, or not in a solvent, under an oxygen atmosphere. The target catalytic substrate CEES (10–15 μl) is added, and irradiated with ultraviolet light at a wavelength of 360 nm or blue light at a wavelength of 420 nm. This selectively oxidizes toxic 2-chloroethyl ethyl sulfide (CEES) to non-toxic 2-chloroethyl ethyl sulfoxide (CEESO).

[0011] The technical effects of this invention are as follows: This material is a delayed fluorescence material based on host-guest interaction for the catalytic degradation of mustard gas mimic CEES. Under excitation with 360nm ultraviolet light or 420nm blue light, it can produce delayed fluorescence with a lifetime of approximately 200ns, effectively utilizing the triplet energy level. The triplet exciton transfers energy to the ground-state oxygen (… 3 O2) is converted into singlet oxygen ( 1 O2), and 1 O2 can selectively convert mustard gas simulant CEES into non-toxic 2-chloroethyl ethyl sulfoxide (CEESO) without producing 2-chloroethyl ethyl sulfone (CEESO2). Therefore, this material can efficiently and rapidly photocatalytically degrade mustard gas simulant.

[0012] The advantages of this invention are: (1) Through the rational design of the host-guest structure of the delayed fluorescence (DF) material, efficient modulation of the excited state is achieved. Under photoexcitation, the triplet exciton transfers energy to the ground state oxygen (3 O2) is converted into singlet oxygen ( 1 (2) The novel host-guest delayed fluorescence material prepared can rapidly catalyze the degradation of mustard gas simulants in solvent-free conditions, achieving a CEES degradation rate of over 99% within 30 minutes under an oxygen atmosphere and ultraviolet light irradiation with an emission wavelength of 360 nm. (3) The material is simple and feasible to synthesize. The conditions required for the material to catalyze the degradation of mustard gas simulants are mild. This material is a safe and reliable material with great potential for the fabrication of devices to prevent and treat the degradation of mustard gas. Attached Figure Description

[0013] Figure 1 This refers to the composition of the material described in this invention.

[0014] Figure 2-1 , Figure 2-2 , Figure 2-3 This is a characterization diagram of the photophysical properties of the material described in this invention.

[0015] Figure 3 This is a paramagnetic resonance spectrum of the material described in this invention for singlet oxygen capture.

[0016] Figure 4 This is a nuclear magnetic resonance (NMR) spectrum monitoring image of the material described in this invention catalytically degrading CEES in deuterated methanol under 420 nm blue light emission in an oxygen environment.

[0017] Figure 5 This is a nuclear magnetic resonance (NMR) spectrum monitoring image of the material described in this invention catalytically degrading CEES in deuterated methanol under ultraviolet light irradiation with a wavelength of 360 nm in an oxygen environment.

[0018] Figure 6 This is a nuclear magnetic resonance spectrum monitoring image of the material described in this invention under solvent-free ultraviolet light irradiation at a wavelength of 360 nm in an oxygen environment to detect degradation during a CEES experiment.

[0019] Figure 7 This is a time-conversion rate diagram of the catalytic degradation of CEES by the material described in this invention under blue light irradiation with a wavelength of 420 nm in an oxygen environment.

[0020] Figure 8 This is a time-conversion rate diagram of the catalytic degradation of CEES by the material described in this invention under ultraviolet light irradiation with a wavelength of 360 nm in an oxygen environment.

[0021] Figure 9 The X-ray powder diffraction patterns of the material described in this invention before and after 30 minutes of reaction under blue light irradiation at a wavelength of 420 nm in an oxygen environment.

[0022] Figure 10This is a cycle number-conversion rate graph for the photocatalytic degradation of CEES by the material described in this invention under irradiation with blue light at a wavelength of 420 nm in an oxygen environment. Detailed Implementation

[0023] Example: 83.3 mg (0.05 mmol) PTA was dissolved in 4 ml DMF solvent, and 30.8 mg (0.05 mmol) cadmium nitrate metal salt was dissolved in 4 ml deionized water. The two were mixed and 7.5 mg (0.03 mmol) TPP was added, followed by 4 ml EtOH. The mixture was placed in a 20 ml vial, sonicated for 15 minutes, and then placed in a 92°C oven for a solvothermal reaction for 12 hours.

[0024] After the reaction is complete, the obtained crystals are washed, dried, and filtered. The product is collected and ground to obtain a coordination polymer material with delayed fluorescence properties.

[0025] The coordination polymer material is a host-guest coordination polymer exhibiting a spatial hexahedral configuration, and it can maintain its original spatial configuration in air, demonstrating good stability. The structural formula of this MOF material is: [Cd4(TPP)2(PTA)3(H2O)4] n ·x(Phcz),x=1-2; Among them, TPP=6'-(pyridin-4-yl)-4,2':4',4''-terpyridine, PTA=terephthalic acid, Phcz=9-phenyl-9H-carbazole.

[0026] 10 mg of the MOF material sample was dispersed in 2 ml of deuterated methanol to prepare a suspension. Then, 500 μl of the suspension was added to 2 ml of 2,2,6,6-tetramethylpiperidine (50 mmol / L) solution. After irradiation with blue light at a wavelength of 420 nm for 10 minutes, [the following steps were taken]. 1 O2 testing proved that the material can produce luminescence quenching in an oxygen atmosphere. 1 O2 ( Figure 3 ).

[0027] The material was used as a catalyst. 10 mg was placed in 2 ml of deuterated methanol solution or solvent-free solution. Under an oxygen atmosphere, the target catalytic substrate was added to 10 μl of CEES. The solution was irradiated with visible or ultraviolet light, and the catalytic process was monitored by nuclear magnetic resonance spectroscopy to carry out the photocatalytic reaction.

[0028] Under irradiation with blue light emitted at a wavelength of 420 nm, this material can selectively oxidize the toxic mustard gas mimic 2-chloroethyl ethyl sulfide (CEES) to the non-toxic 2-chloroethyl ethyl sulfoxide (CEESO), without producing the highly toxic compound 2-chloroethyl ethyl sulfone (CEESO2). 1 HNMR monitoring showed that under blue light irradiation at a wavelength of 420 nm, the material converted more than 99% of CEES into the non-toxic oxidation product CEESO within 30 minutes. Figure 4 ); Under ultraviolet light irradiation at a wavelength of 360 nm, this material converts more than 99% of CEES into the non-toxic oxidation product CEESO within 15 minutes. Figure 5 Even under solvent-free conditions with ultraviolet light irradiation at an emission wavelength of 360 nm, this material can convert more than 99% of CEES into the non-toxic oxidation product CEESO within 30 minutes. Figure 6 ).

[0029] In stark contrast, without the aforementioned MOF material, the reaction conversion rate decreased significantly. Figure 7 , Figure 8 This indicates that the material significantly accelerates the oxidation rate. After catalysis, the catalyst is separated by centrifugation and can then be reused.

[0030] After the reaction, the X-ray powder diffraction of the material did not change significantly, indicating that the material maintained good stability during the reaction. Figure 9 After three reaction cycles, the CEES conversion rate did not decrease, indicating that the material exhibits good stability during long-term, multiple-cycle catalysis. Figure 10 The required light wavelength range includes ultraviolet and blue light, namely 360 nm and 420 nm; the required oxygen content is pure oxygen; and the required catalyst loading is 1% to 2% of the molar amount of mustard gas simulant 2-chloroethyl ethyl sulfide.

Claims

1. A coordination polymer material with delayed fluorescence properties, characterized in that... The structural formula of this material is: [Cd₄(TPP)₂(PTA)₃(H₂O)₄] n ·x(Phcz),x=1-2; Among them, TPP=6'-(pyridin-4-yl)-4,2':4',4''-terpyridine, PTA=terephthalic acid, Phcz=9-phenyl-9H-carbazole.

2. The coordination polymer material with delayed fluorescence properties according to claim 1, characterized in that... It is a host-guest coordination polymer that exhibits a spatial hexahedral configuration with crystal lengths ranging from 50 μm to 200 μm. It can maintain its original spatial configuration in air and has good stability.

3. The coordination polymer material with delayed fluorescence properties according to claim 1, characterized in that... This material can produce delayed fluorescence with an average lifetime of 180–240 ns when excited by ultraviolet light with an emission wavelength of 360 nm or blue light with an emission wavelength of 420 nm.

4. The coordination polymer material with delayed fluorescence properties according to claim 1, characterized in that... The coordination polymer material with delayed fluorescence properties is prepared from 2,4,6-tris(pyridin-4-yl)pyridine (TPP), terephthalic acid (PTA), N-phenylcarbazole (Phcz), and cadmium salt.

5. A method for preparing a coordination polymer material with delayed fluorescence properties as described in any one of claims 1-4, characterized in that... Includes the following steps: (1) Dissolve 0.05-0.1 mmol PTA in 3-5 ml DMF solvent, dissolve 0.05-0.1 mmol cadmium salt in 3-5 ml deionized water, mix the two and add 0.03-0.06 mmol TPP, then add 3-5 ml EtOH, mix, sonicate for 15-20 minutes, and then place in a 92-100℃ oven for a solvothermal reaction for 12-24 hours; (2) After the reaction is complete, yellow-green rod-shaped crystals are obtained. The crystals are washed and filtered with DMF, water or anhydrous ethanol solvent. After drying for 3-5 hours, the product is collected and ground to obtain yellow-green powder, which is the coordination polymer material with delayed fluorescence properties.

6. The application of a coordination polymer material with delayed fluorescence properties as described in any one of claims 1-4, characterized in that... The coordination polymer material is used in highly efficient singlet oxygen catalytic oxidation reactions.

7. The application of the coordination polymer material with delayed fluorescence properties according to claim 6, characterized in that... The coordination polymer material with delayed fluorescence properties is used as a catalyst. 10-15 mg of the coordination polymer material is placed in 1-2 ml of deuterated methanol solution, methanol solution, or acetonitrile solution, or not placed in a solvent, and then added to a 20-50 mmol / L 2,2,6,6-tetramethylpiperidine (TEMP) solution. Under an oxygen atmosphere, the material is irradiated with ultraviolet or visible light, causing the luminescence of the coordination polymer material to quench, generating singlet oxygen. 1 O2, TEMP captures singlet oxygen 1 O2 generates TEMPO.

8. The application of a coordination polymer material with delayed fluorescence properties as described in any one of claims 1-4, characterized in that... The coordination polymer material is used for the catalytic degradation of chemical warfare agents.

9. The application of the coordination polymer material with delayed fluorescence properties according to claim 8, characterized in that... Using the coordination polymer material as a catalyst, 10-15 mg of the coordination polymer material is placed in 1-2 ml of deuterated methanol solution, methanol solution, or acetonitrile solution, or not placed in a solvent. Under an oxygen atmosphere, 10-15 μl of the target catalytic substrate 2-chloroethyl ethyl sulfide (CEES) is added, and the toxic 2-chloroethyl ethyl sulfide (CEES) is selectively oxidized to non-toxic 2-chloroethyl ethyl sulfoxide (CEESO) by irradiation with visible or ultraviolet light.

Citation Information

Patent Citations

  • Sorption filter material and use thereof

    CN102006929A

  • Preparation method and application of cobalt-based metal organic framework Co-MOF material

    CN112280051A